Educational experience in virtuality. Perceptions of future educators about an teaching agency under construction - Rigo, Daiana Yamila (2022)
The research that is presented aimed to study the perceptions about the development of the agency of a group of university students, throughout an educational experience mediated by Information and Communication Technologies in the context of a teacher training program. The study was framed in an interpretative qualitative design, in which 44 subjects enrolled in various professorships of the UNRC, Argentina participated. For data collection, group interviews were used, analyzed with ATLAS.ti. The emerging categories account for an agency that is defined as interactive and contextual that is built, together with others, in the face of the challenges that arise in real and uncertain educational situations. Thus, experiences traversed by digital technologies allow students to display diverse actions and behaviors. The results allow us to rethink the educational practices that are framed within institutional environments, offer genuine spaces for discussion and exchanges between disciplines to generate breaks in routine practices in order to integrate new digital resources into the training of future teachers.